Upregulated LncZBTB39 in pre-eclampsia and its effects on trophoblast invasion and migration via antagonizing the inhibition of miR-210 on THSD7A expression. (May 2020) - Tian, Jing; Liu, Yamin; Hu, Mingyu; Zheng, Yangxi; Xu, Ping; Zhang, Lan; Liao, Jiujiang; Wu, Yue; Wen, Li; Tong, Chao; Yan, Jianying; Qi, Hongbo; et al.
Highlights: Upregulation of lncZBTB39 in PE-complicated human placentas was identified by unbiased high throughput screening. LncZBTB39 inhibits trophoblastic invasion and migration. LncZBTB39 regulates THSD7A transcription by antagonizing miR210. Abstract: Objective: Pre-eclampsia (PE) is a major cause of maternal morbidity and mortality, but its etiology remains to be elucidated. Accumulating evidence suggests that placental long noncoding RNAs (lncRNAs) might contribute to the pathogenesis of pre-eclampsia. Study Design: In the present study, the expression levels of lncRNAs in human placenta were first determined by microarray analysis and then validated by secondary RT-qPCR and FISH. LncZBTB39 expression manipulation in HTR8/SVneo trophoblast cells was achieved by shRNA and plasmid transfection. Then, the invasion and migration of lncZBTB39-deficient and lncZBTB39-overexpressing trophoblast cells were evaluated by transwell assays and wound-healing assays, respectively. MMP2 activity was measured by gelatin zymography. The downstream target genes of lncZBTB39 were then identified by a transcriptomic microarray, followed by RT-qPCR validation. Results: We found that lncZBTB39 was upregulated in PE-complicated human placentas, and overexpression of lncZBTB39 inhibited invasion and migration, as well as MMP2 activity in HTR8/SVneo cells, while downregulation of lncZBTB39 enhanced invasion, migration and MMP2 activity. In addition, THSD7A expression was elevated by lncZBTB39 overexpression but reduced in lncZBTB39-deficient cells; moreover, lncZBTB39 antagonized the inhibitory effects of miR-210 on THSD7A expression. Conclusion: PE-complicated placentas are associated with upregulated lncZBTB39, which negatively regulates trophoblast invasion and migration, most likely by preserving the expression of THSD7A mRNA through sponging miR-210. The results of this study not only provide novel evidence that lncRNAs regulate trophoblastic activities but also suggest that lncZBTB39 may be a potential interventional target for PE.